Comparison of Dexmedetomidine and Dexamethasone Used as Adjuvant to Ropivacaine in Ultrasound-guided Supraclavicular Brachial Plexus Block: An Observational Study - Shaiqa Manzoor; Masarat Ara (Academia Anesthesiologica International, 2022)
Background: Supraclavicular brachial plexus block is one of the preferred technique to provide perioperativeanaesthesia and analgesia for upper limb surgical procedures. The duration of block can be extended by the addition of various adjuvants. Our aim was to compare the efficacy of dexamethasone and dexmedetomidine as an adjuvant to ropivacaine in extending the duration of supraclavicular brachial plexus block and quality of postoperative analgesia. Subjects and Methods: This prospective observational study was carried out in 60 American Society of Anaesthesiologists gradeI-III patients, aged18-70years scheduled for upper limb surgeries randomly allocated in to two groups with each group consisting of 30 patients. All patients under ultrasound?guided supra clavicular brachial plexus block received 25 ml of 0.5% ropivacaine. Along with ropivacaine, GroupDX patients received 8 mg(2 ml) of Dexamethasone and  Group DM received 1 gkg-1 (2ml) of dexmedetomidine. Results: We noted a significantly extended duration of motor block (853.5 +/- 115 min vs628.6 +/- 135 min) and extended duration of complete analgesia (1374.2 +/- 185.4vs 1084.2 +/- 156.5min) in dexmedetomidine group compared todexamethasone group. The postoperative pain scores were significantly lower in dexmedetomidine group andtotal consumption of intravenous diclofenac sodium in 24 hours was less in dexmedetomidine group. No adverse effects were noted in either group. Patient satisfaction score was comparable inboththe  group. Conclusion: Dexmedetomidine when used as adjuvant to ropivacaine for supraclavicular brachial plexus blockprolongs the duration of block and improves the quality of postoperative analgesia as compared to dexamethasone without any serious side effects.